Exploring the Mediating Effect of Work Motivation on the Relationship between Work Environment, Job Stress, and Performance in the Public Sector - Nanda Suryadi; Yayu Kusdiana; Arie Yusnelly; Tilovmurodov Dostonbek Furqat Ugli (Yayasan Pendidikan Islam Al-Matani, 2025)
This study investigates the mediating role of work motivation in the relationship between work environment, job stress, and employee performance at the General Bureau of the Riau Provincial Government. The research adopts a confirmatory and explanatory approach to examine causal relationships among variables based on established theoretical frameworks in human resource management. A saturated sampling technique was applied, involving all 100 employees of the General Bureau as respondents. Data were analyzed using Structural Equation Modeling with the Partial Least Squares approach (SEM-PLS) through SmartPLS 4.0. The results indicate that the work environment has a significant positive effect on work motivation and employee performance, while job stress has a negative influence on both motivation and performance. Work motivation is proven to play a crucial mediating role, strengthening the positive impact of a supportive work environment on performance and buffering the adverse effects of job stress. These findings suggest that employee performance in the public sector is not only shaped by structural and psychological working conditions but is also strongly driven by the level of internal motivation. This study contributes to the literature by providing empirical evidence on the integrative model of work environment, job stress, motivation, and performance within a provincial government context. Practically, the findings imply that public sector managers should prioritize the creation of a conducive work environment, effective stress management, and motivational enhancement programs to improve employee performance and organizational effectiveness.